Cereal yield and water requirements in response to irrigation and soil fertility management in a changing climate: a case of Tulsipur, western Nepal - Zuber, Md.; Kalauni, N.; Shrestha, Nirman; Pandey, V. P.; Pokharel, B. (IWA Publishing, 2025)
Climate change is projected to notably impact water requirements and crop yield; therefore, it is imperative to quantify climate risk and devise climate-resilient field management practices. This study applied the AquaCrop model to Tulsipur, a sub-metropolitan city located in Western Nepal. The model was calibrated and validated on a field scale, and various scenarios were analysed for baseline (2010–2020) and future (2021–2100) periods to formulate workable management strategies for irrigation and fertilizer applications. Results showed that a deficit irrigation strategy could lead to 81% fewer requirements for irrigation in rice and 24% in wheat at the cost of a minimal (~1%) reduction in yield. Water requirement is projected to decrease and crop yield to increase for both crops for all future scenarios, except wheat water requirement, where water requirement is projected to increase by up to 13% in the future. Rainfed irrigation leads to extremely high variance in crop yields. Deficit irrigation under the nationally recommended fertilizer dose is recommended as a better option to develop climate resiliency in cereal yield in the study area.